2022
DOI: 10.1038/s41467-022-34239-z
|View full text |Cite
|
Sign up to set email alerts
|

FOXQ1 recruits the MLL complex to activate transcription of EMT and promote breast cancer metastasis

Abstract: Aberrant expression of the Forkhead box transcription factor, FOXQ1, is a prevalent mechanism of epithelial-mesenchymal transition (EMT) and metastasis in multiple carcinoma types. However, it remains unknown how FOXQ1 regulates gene expression. Here, we report that FOXQ1 initiates EMT by recruiting the MLL/KMT2 histone methyltransferase complex as a transcriptional coactivator. We first establish that FOXQ1 promoter recognition precedes MLL complex assembly and histone-3 lysine-4 trimethylation within the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Our data show that FOXQ1 is signi cantly upregulated in radioresistant TNBC cells, suggesting its involvement in TNBC radioresistance. Previous studies have reported that FOXQ1 can activate EMT and promote metastasis and chemoresistance in breast cancer [18,33]. Consistently, our results indicate that FOXQ1 plays a pivotal role in the maintenance of radioresistance in TNBC cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data show that FOXQ1 is signi cantly upregulated in radioresistant TNBC cells, suggesting its involvement in TNBC radioresistance. Previous studies have reported that FOXQ1 can activate EMT and promote metastasis and chemoresistance in breast cancer [18,33]. Consistently, our results indicate that FOXQ1 plays a pivotal role in the maintenance of radioresistance in TNBC cells.…”
Section: Discussionsupporting
confidence: 91%
“…However, overexpression of FOXQ1 alone is not su cient to induce the radioresistance in TNBC cells. Mitchell et al [33] demonstrated that FOXQ1 recruits the MLL/KMT2 histone methyltransferase complex to regulate gene expression. Meng et al [18] reported that FOXQ1 can interact with TWIST1 to modulate downstream target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, FOXQ1 has been described as oncogene in several human cancers [45,[52][53][54], and will be discussed in more detail in this thesis (see section 1.2.3).…”
Section: Fox Factors In Cancermentioning
confidence: 97%
“…FOXQ1 has been primarily associated with the direct transcriptional regulation of target genes that drive EMT, such the downregulation of epithelial CDH1 expression and the upregulation of the CDH2 mesenchymal marker [40,72]. Additionally, other mechanisms such as the regulation of other EMT-associated transcription factors [53,73,74] or the induction of changes in the chromatin status have been described [52].…”
Section: Forkhead Box Q1mentioning
confidence: 99%
“…The transcription factor forkhead box Q1 (FOXQ1), a member of the FOX family(8), contributes to a variety of physiological processes, including cellular senescence (9), glucose metabolism (10), lactate synthesis (11), and cardiac brosis (12). FOXQ1 also acts as a signi cant role in the biological processes that contribute to malignancy, including invasion, apoptosis, and epithelial-mesenchymal transition (13), in diverse cancers, including breast cancer, rectal cancer, and intrahepatic cholangiocarcinoma (14)(15)(16)(17)(18). Nevertheless, the role of FOXQ1 in PC have not been clari ed.…”
Section: Introductionmentioning
confidence: 99%